Czy jesteśmy gotowi na stosowanie RODO? Wybrane zagadnienia z zakresu funkcjonowania administracji publicznej - Jabłoński, Mariusz; Sakowska-Baryła, Marlena; Wygoda, Krzysztof (Publishing House eBooki.com.pl, 2018)
The monograph is an element of the discussion on the application of GDPR by public authority's in the sphere of public administration. Due to the scope of the subject matter, it focuses on several key issues. The first problem is to match the definition of the controller of the personal data to the specifics of the operation of public administration. The primary ability to perform all the controller's duties seems to be particularly important here. The second - the conditions for legalizing data processing to the conditions of the public administration. The third is the actual scope of the controller's responsibilities, including his relationship with the data protection officer. The fourth issue is the conditions to entrust the processing of personal data and the principle of correct implementation of this process. The last issue includes the implementation of information and communication procedures, which requires the solution of many complex problems, including identification of the application and identity of the applicant (data subject), keeping appropriate deadlines and a skillful solution of the issue of fees.
Keywords: personal data; GDPR; principles relating to processing; controller; responsibility of the controller; procesor; data protection officer; right to information; data protection impact assessment; administrative fines; public authority or body; public administration